2015
DOI: 10.1002/2014tc003660
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the flexural evolution of the Amiran and Mesopotamian foreland basins of NW Zagros (Iran-Iraq)

Abstract: The evolution of the Amiran and Mesopotamian flexural basins of the Zagros belt is approached by coupled 2-D forward modeling of orogenic wedge formation, lithospheric flexural isostasy, and stream power erosion/transport/sedimentation. Thrust geometries and sequence of emplacement derived from geometric and kinematic models presented here are the inputs to our evolutionary model, constrained by basin geometry, sediment volume, and topography. Modeling results confirm that the Zagros flexural basins evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 90 publications
3
60
0
Order By: Relevance
“…We therefore estimate the range of possible values required to fit jointly the foreland depth and FAA to between 38 and 60 km. This range of values is consistent with the equivalent elastic thickness of the lithosphere determined in previous studies based on the analysis of 1-D profiles in the eastern sector of our study area (about 50 km, Snyder & Barazangi 1986;Saura et al 2015). It is also consistent with the equivalent elastic thickness mapped from the coherence between the topography and the gravity field (Chen et al 2015), which shows a gradient from about 90 km for the Arabian Platform south of the Mesopotamia basin to about 30 km beneath the Zagros.…”
Section: Implications For the Rheological Layering Of The Continentalsupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore estimate the range of possible values required to fit jointly the foreland depth and FAA to between 38 and 60 km. This range of values is consistent with the equivalent elastic thickness of the lithosphere determined in previous studies based on the analysis of 1-D profiles in the eastern sector of our study area (about 50 km, Snyder & Barazangi 1986;Saura et al 2015). It is also consistent with the equivalent elastic thickness mapped from the coherence between the topography and the gravity field (Chen et al 2015), which shows a gradient from about 90 km for the Arabian Platform south of the Mesopotamia basin to about 30 km beneath the Zagros.…”
Section: Implications For the Rheological Layering Of The Continentalsupporting
confidence: 92%
“…They therefore concluded that subsurface loads or dynamic stresses were needed in addition to the topographic load. More recently, Saura et al (2015) modelled a section of the Zagros foreland and reached the conclusion that additional subcrustal load is necessary to account for the observed flexure.…”
Section: Introductionmentioning
confidence: 99%
“…The total shortening is 20 km, 8 km of which being associated to the thin-skinned Satiary and Herta thrust systems to the NE of the Marakhil Anticline. As previously mentioned, these thrusts are truncated by the High Zagros Fault, which in this area was active during the Late Cretaceous to Paleocene interval (Karim et al, 2011;Vergés et al, 2011;Saura et al, 2015). Fault, which forms part of a thrust system splaying from a mid-crustal decollement (Vergés et al, 2011), similar to that documented in other FTBs (Cristallini and Ramos, 2000;Butler et al, 2004;Lacombe and Bellahsen, 2016).…”
Section: Balancing the Cross-sectionsupporting
confidence: 56%
“…The closure of the Neo-Tethys Ocean during the Late Cretaceous led to the formation of a flexural basin, filled by a ca. 2 km thick Maastrichtian to Eocene succession (Hessami et al, 2001;Homke et al, 2009;Vergés et al, 2011;Saura et al, 2015), evolving from deep-marine marls and limestones to a prograding wedge of deep marine to continental clastic sediments. This first foredeep infill is overlain by about 500 m of shallowwater carbonates of the Shahbazan and Asmari Fm (Oligocene-lower Miocene), passing upward to lower Miocene evaporites.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Time steps were constructed by forward modeling in Midland Valley Move© software. (a) Pre‐Zagros (>80 Ma) configuration of the Arabian passive margin and Neotethys suprasubduction zone based on Verges et al (), Saura et al (), and Moghadam and Stern (). (b) Proto‐Zagros ophiolite obduction (80–56 Ma): emplacement of oceanic and allochthonous thrust sheets upon Arabian margin; flexural development of Amiran‐Kashghan foreland basin (Homke et al, ; Saura et al, ).…”
Section: Discussionmentioning
confidence: 99%